Survival and Physiological Responses of Greenlip Abalone (Haliotis laevigata) under Simulated Live Transport - Frederika Niken Restu Kurnaningtyas; Ishaaq Saputra; Eko Hendri Gunawan (Department of Aquaculture, 2022)
Greenlip abalone (Haliotis laevigata) are high-value marine bivalves. In order to preserve the quality, most of edible aquatic animals were transported in live conditions. In addition, keep the condition at low temperature is considered as the best way to reduce the stress level of the animal. However, this method is still poorly understood in greenlip abalone. The present study examines the effects of pre-cooled (±14 °C) and non-precooled (±21 °C) temperature treatments on survival and physiological responses such as total haemocyte count, phagocytic assay, lysosomal assay, and lactate of live abalone during transport simulation at time intervals of 0, 12, 24, 36 and 48 hours. Results indicated that pre-cooling treatment prior to transport increased the survival rate and minimised weight loss. The lactate levels were significantly higher in the abalones that were not cooled prior to transport. Both animals that were pre-cooled and those that were not cooled prior to aerial transport simulation showed increases in total haemocyte count and a decrease in phagocytic activity, which indicates that live transport has an impact on their immunity. The present study indicated that the importance of pre-cooling treatment before transportation to preserve the condition of live abalone.